RADIOGRAPHIC CHARACTERISTICS OF HIP JOINT IN ADULT PATIENTS HAVING DYSPLASIA WHO HAVE BEEN TREATEED BY GANZ OSTEOTOMY - Qahramanov, A.G.; Atіlla B.S.; Alpaslan, M.Sh.; Tokgezogli, M.N.; Aksoy, D.M. (World of Medicine and Biology, 2015)
The aim of this study was to analiz of radiographic parameters of hip joint in adult patients having dysplasia who have been treated by Ganz osteotomy. There were reexamined 71 patients (83 joints) who have been treated by Ganz osteotomy within 8 years period on the average. There were detected improvement in Tonnis angle by 24º; in Viberg angle by 32; Leguence angle by 34; covering of femoral head by 26%; and medialization by 3 mm during evaluation of radiographic parameters. Harris Hip Score was 62 before the surgical operation and 87 – after. Thus, there was noted the improvement in parameters of radiographic indicators of reorientation of acetabulum as well as in functional indicator of hip joint.